Bibliometric and Visualization Analysis of Research Hotspots in Field of Smart Water Conservancy - WANG Zhankui; PAN Wuhan; WU Jianxing; ZHANG Jianchang; TAN Yu; WU Xuefei; WEI Guoqing (Renmin Zhujiang)
In order to comprehensively understand the development status in the field of smart water conservancy in China, the research literature in the field of smart water conservancy from 2016 to 2023 was measured and visualized using the China National Knowledge Infrastructure (CNKI) database and CiteSpace software. Based on the statistical analysis of the annual number of publications, journal sources, highly cited literature, main authors, research institutions, keywords, and other elements, the research knowledge base and hot topics in the field of smart water conservancy were summarized. In terms of time and space, the number of publications in this field has shown an overall exponential growth trend over time, with slow growth in the early period and rapid growth in the recent period. The data indicates that during 2016—2023, the journal with the highest number of publications in the field of smart water conservancy is Water Resources Informatization, and the scholar publishing the highest number of research articles is Jiang Yunzhong. The article titled Understanding and Thinking of Smart Water Conservancy received the most citations. Currently, the China Institute of Water Resources and Hydropower Research is the most active and extensive scientific research organization studying smart water conservancy. Digital twins, big data, and data floors are deeply studied in smart water conservancy construction. Finally, the digital twin technology is analyzed in the water conservancy project in detail, which shows that the digital twin technology is the frontier trend of water conservancy development in the future.